Tracing the Trend of Research on Surrogacy: A Scientometric Analysis - Ahmadi, Ashiya; Raza, Ali; Ahmed, Sufia (Journal of Information and Knowledge, 2019)
The current work examines surrogacy-related research all over the world during the period 2007-2016. Data were obtained from the Web of Science Core Collection. Several steps were taken to identify articles on surrogacy and ultimately, any article that has the word ‘surrogacy’ in the paper title, abstract; author keywords and KeyWords Plus were identified. The process yielded 435 articles for further analysis. It was anticipated that the results would provide insight into the existing research trends and help researchers to discern the direction of science in surrogacy research in world. Such a comprehensive overview of current state of surrogacy research is important for both researchers as well as policy makers where the research is taking place.